Kavitationsdetektion mittels Self-Sensing-Ultraschallwandler - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (tm - Technisches Messen)
Eine Vielzahl von Prozessen in der Chemie und Verfahrenstechnik kann durch Ultraschall positiv beeinflusst werden. Oftmals ist ultraschallinduzierte Kavitation der Hauptwirkmechanismus für die positiven Effekte der Beschallung. Daher ist es notwendig die Kavitationsaktivität während des Prozesses zu quantifizieren um die Beschallung für den jeweiligen Prozess optimal gestalten und überwachen zu können. Eine Möglichkeit der prozessbegleitenden Kavitationsdetektion ist die Auswertung der akustischen Emissionen von oszillierenden und kollabierenden Kavitationsblasen mittels Drucksensoren in der Flüssigkeit. Raue Prozessrandbedingungen wie hohe Temperaturen oder aggressive Flüssigkeiten erschweren es jedoch geeignete Sensoren zu finden. Als Alternative wurde daher die Nutzbarkeit der Rückwirkung von Kavitationsereignissen auf das elektrische Eingansgssignal des Ultraschallwandlers zur Quantifizierung von Kavitation untersucht. Die experimentelle Analyse hat ergeben, dass das Einsetzen und in einigen Fällen auch die Art der Kavitation auf Basis der Rückwirkung auf das Stromsignal des Ultraschallwandlers bestimmt werden kann. Die Stärke der Kavitation war hingegen nicht aus den Stromsignalen abzuleiten.
Keywords: Kavitationsdetektion; Self-Sensing; So- nochemie; Ultraschallwandler

Thick KNbO 3 films deposited by ultrasonic-assisted hydrothermal method - Kudo, Ryo; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Acoustical Science and Technology)

Improving the bond quality of copper wire bonds using a friction model approach - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (Electronic Components and Technology Conference (ECTC), 2014 IEEE 64th)
In order to increase mechanical strength, heat dissipation and ampacity and to decrease failure through fatigue fracture, wedge copper wire bonding is being introduced as a standard interconnection method for mass production. To achieve the same process stability when using copper wire instead of aluminum wire a profound understanding of the bonding process is needed. Due to the higher hardness of copper compared to aluminum wire it is more difficult to approach the surfaces of wire and substrate to a level where van der Waals forces are able to arise between atoms. Also, enough friction energy referred to the total contact area has to be generated to activate the surfaces. Therefore, a friction model is used to simulate the joining process. This model calculates the resulting energy of partial areas in the contact surface and provides information about the adhesion process of each area. The focus here is on the arising of micro joints in the contact area depending on the location in the contact and time. To validate the model, different touchdown forces are used to vary the initial contact areas of wire and substrate. Additionally, a piezoelectric tri-axial force sensor is built up to identify the known phases of pre-deforming, cleaning, adhering and diffusing for the real bonding process to map with the model. Test substrates as DBC and copper plate are used to show the different formations of a wedge bond connection due to hardness and reaction propensity. The experiments were done by using 500 $μ$m copper wire and a standard V-groove tool.
Keywords: adhesion; circuit reliability; deformation; diffusion; fatigue cracks; friction; interconnections; lead bonding; van der Waals forces; Cu; adhering process; adhesion process; ampacity improvement; bond quality improvement; cleaning process; diffusing process; fatigue fracture failure; friction energy; friction model; heat dissipation; mechanical strength; piezoelectric triaxial force sensor; predeforming process; size 500 mum; total contact area; van der Waals forces; wedge copper wire bonding; Bonding; Copper; Finite element analysis; Force; Friction; Substrates; Wires

Self-Sensing Ultrasound Transducer for Cavitation Detection - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (2014 IEEE International Ultrasonics Symposium Proceedings)
Cavitation monitoring is desired to optimize the sonication for diverse sonochemical processes and to detect changes or malfunctions during operation. In situ cavitation measurements can be carried out by detection of the acoustic emissions of cavitation bubbles by sensors in the liquid. However, in harsh environments sensors might not be applicable. Thus, the impact of cavitation on the electrical signals of a piezoelectric transducer has been analyzed as alternative method to measure the threshold, strength and type of cavitation. The applicability has been tested in three different setups to evaluate the general- izability of extracted indicators. In all setups indicators for the cavitation thresholds could be derived from the current signal. In two setups features showed two thresholds that may be linked to the types of cavitation. However, only one feature derived from the current signal in one particular setup correlated to the strength of cavitation. Cavitation detection based on the current signal of the transducer is a useful method to detect cavitation in harsh environments and without perturbing the sound field. Once appli- cable indicators have been identified, they may easily be tracked during the process. However, for more detailed studies about the cavitation activity and its spatial distribution, measurements with in situ sensors are recommended.

Reliability analysis of ultrasonic power transducers - Hemsel, Tobias; Bornmann, Peter; Morita, Takeshi; Sondermann-Wölke, Christoph; Sextro, Walter (Archive of Applied Mechanics)
Keywords: Reliability; Ultrasonic power transducers; FMEA

High-velocity operation of piezoelectric inertia motors: experimental validation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Archive of Applied Mechanics)
Piezoelectric inertia motors use the inertia of a body to drive it by means of a friction contact in a series of small steps. It has been shown previously in theoretical investigations that higher velocities and smoother movements can be obtained if these steps do not contain phases of stiction (''stick-slip`` operation), but use sliding friction only (''slip-slip`` operation). One very promising driving option for such motors is the superposition of multiple sinusoidal signals or harmonics. In this contribution, the theoretical results are validated experimentally. In this context, a quick and reliable identification process for parameters describing the friction contact is proposed. Additionally, the force generation potential of inertia motors is investigated theoretically and experimentally. The experimental results confirm the theoretical result that for a given maximum frequency, a signal with a high fundamental frequency and consisting of two superposed sine waves leads to the highest velocity and the smoothest motion, while the maximum motor force is obtained with signals containing more harmonics. These results are of fundamental importance for the further development of high-velocity piezoelectric inertia motors.
Keywords: Inertia motor; High velocity; Stick-slip motor; Slip-slip operation; Friction parameter identification

Synthesis of lead-free piezoelectric powders by ultrasonic-assisted hydrothermal method and properties of sintered (K0.48Na0.52)NBO3 ceramics - Isobe, G.; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics, Ferroelectrics, and Frequency Control, IEEE Transactions on)
(K,Na)NbO3 ceramics have attracted much attention as lead-free piezoelectric materials with high piezoelectric properties. High-quality (K,Na)NbO3 ceramics can be sintered using KNbO3 and NaNbO3 powders synthesized by a hydrothermal method. In this study, to enhance the quality factor of the ceramics, high-power ultrasonic irradiation was employed during the hydrothermal method, which led to a reduction in the particle size of the resultant powders.
Keywords: Q-factor; ceramics; crystal growth from solution; particle size; piezoelectric materials; potassium compounds; powders; sintering; sodium compounds; ultrasonic effects; (K0.48Na0.52)NbO3; KNbO3 powders; NaNbO3 powders; high-power ultrasonic irradiation; lead-free piezoelectric materials; lead-free piezoelectric powders; particle size reduction; piezoelectric properties; quality factor; sintered (K0.48Na0.52)NbO3 ceramics; sintering; ultrasonic-assisted hydrothermal method; Acoustics; Ceramics; Lead; Piezoelectric materials; Powders; Radiation effects; Transducers

Increasing the power of piezoelectric energy harvesters by magnetic stiffening - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
A piezoelectric cantilever beam with a tip mass at its free end is a common energy harvester configuration. This article introduces a new principle of designing such a harvester that increases the generated power without changing the resonance frequency of the harvester: the attraction force between two permanent magnets is used to add stiffness to the system. This magnetic stiffening counters the effect of the tip mass on the efficient operation frequency. Five set-ups incorporating piezoelectric bimorph cantilevers of the same type in different mechanical configurations are compared theoretically and experimentally to investigate the feasibility of this principle: theoretical and experimental results show that magnetically stiffened harvesters have important advantages over conventional set-ups with and without tip mass. They generate more power while only slightly increasing the deflection in the piezoelectric harvester and they can be tuned across a wide range of excitation frequencies.

Enhanced energy harvesting using multiple piezoelectric elements: Theory and experiments - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Power and bandwidth of piezoelectric harvesters can be increased by using multiple piezoelectric elements in one harvester. In this contribution, a novel energy harvesting cantilever array with magnetic tuning including three piezoelectric bimorphs is investigated theoretically and experimentally, with a good agreement between model and experiment. Other than harvester designs proposed before, this array is easy to manufacture and insensitive to manufacturing tolerances because its optimum operation frequency can be re-adjusted after fabrication. Using the superposition principle, the Butterworth-Van Dyke model and a mechanical lumped parameters model, the generated voltage and current are determined analytically. Formulas for calculating the power generated by array harvesters with an arbitrary number of piezoelectric elements connected in series or in parallel are derived. It is shown that optimum harvester design must take both the connected load and the operating frequency into account. Strategies for connecting multiple bimorphs to increase the maximum generated power and/or enhance the bandwidth compared to a single bimorph harvester are investigated. For bandwidth enhancement it is essential that individual rectifiers are used for the bimorphs. An example with three bimorphs shows that, depending on the chosen tuning strategy, the power is increased by about 340% or the bandwidth is increased by about 500%, compared to one single bimorph.
Keywords: Energy harvesting; Cantilever array; Bandwidth; Power increase

Characteristics of Piezoelectric Energy Harvesters in Autonomous Systems - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Proceedings of 10th International Workshop on Piezoelectric Materials and Applications and 8th Energy Harvesting Workshop, Hannover, Germany, 14.-17.7.2013)
A basic autonomous system powered by a piezoelectric harvester contains three components apart from the harvester: a fullwave rectifier, a reservoir capacitor and an electronic device performing the primary task of the system. In this contribution, a model describing the operation of such a system is derived. It is found that in steady-state operation, the piezoelectric harvester experiences two alternating load conditions due to the rectification process. These alternating load conditions can have a significant effect on the operation of the harvester and must be considered in the design of autonomous systems. The results also show that such an autonomous system works efficiently if it is connected to a high impedance load and excited by a frequency matching the anti-resonance frequency of the piezoelectric harvester.
Keywords: Energy harvesting; harvester modeling; load dependence; generated voltage

A friction based approach for modeling wire bonding - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (IMAPS 2013, 46th International Symposium on Microelectronics)
A model approach for wedge/wedge bonding copper wire is presented. The connection between wire and substrate is based on a variety of physical effects, but the dominant one is the friction based welding while applying ultrasound. Consequently, a friction model was used to investigate the welding process. This model is built up universal and can be used to describe the formation of micro welds in the time variant contact area between wire and substrate. Aim of the model is to identify the interactions between touchdown, bond normal force, ultrasonic power and bonding time. To do so, the contact area is discretized into partial areas where a Point Contact Model is applied. Based on this approach it is possible to simulate micro and macro slip inside the contact area between wire and substrate. The work done by friction force is a main criterion to define occurring micro joints which influence the subsequent welding.
Keywords: Wire bonding; friction modeling; wire bond quality; contact element modeling

Leistungs- und Bandbreitensteigerung von Energy-Harvesting-Generatoren für Energieautarke Systeme - Hunstig, Matthias; Al-Ashtari, Waleed; Hemsel, Tobias; Sextro, Walter (9. Paderborner Workshop Entwurf mechatronischer Systeme)

High-Velocity Slip-Slip Operation of Piezoelectric Inertia Motors - Experimental Validation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Proceedings of 10th International Workshop on Piezoelectric Materials and Applications and 8th Energy Harvesting Workshop)
It has been shown previously that ``slip-slip'' operation of piezoelectric inertia motors allows higher velocities and smoother movements than classic ``stick-slip'' operation. One very promising driving option is to use a superposition of multiple sinusoidal signals. In this contribution, previous theoretical results are validated experimentally. The results confirm the theoretical result that for a given maximum frequency, usually defined by the actuator characteristics, a signal with high fundamental frequency and consisting of two superposed sine waves leads to the highest velocity and the smoothest motion. This result is of fundamental importance for the further development of high-velocity piezoelectric inertia motors.
Keywords: Piezoelectric inertia motor; stick-slip motor; driving signal; velocity; smoothness

Modelling the friction contact in an inertia motor - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
Piezoelectric inertia motors, also known as stickslip drives or (smooth) impact drives, use the inertia of a body to drive it by a friction contact in small steps, in the majority of motors composed of a stick phase and a slip phase between the friction partners. For optimizing inertia motors, it is important to understand the friction contact correctly and to measure its properties appropriately. This contribution presents experimental set-ups for measuring the contact force, friction force and relative displacement in an actual inertia motor with a dry friction contact and numerical simulations of the motor operation. The motor uses a pre-stressed multilayer actuator with a displacement in the range of 20 $μ$ m. It is shown that a previously postulated condition for the applicability of simple kinetic friction models is well fulfilled for the investigated motor. The friction contact in the motor is simulated using different kinetic friction models. The input for the friction models is the measured motion of the rod. The models qualitatively reproduce the measured motion but show quantitative deviations varying with frequency. These can be explained by vibrations of the driving rod that are experimentally investigated.
Keywords: Actuator; friction; motor; piezoelectric

Stick-slip and slip-slip operation of piezoelectric inertia drives - Part II: Frequency-limited excitation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
This contribution provides a systematic investigation and performance comparison of different modes of operation for piezoelectric inertia drives. The movement of these motors is classically assumed to consist of steps involving stiction and sliding, resulting in the term ``stick-slip drives''. In the first part of this contribution it has been found that using ideal driving signals, ``slip-slip'' operation without phases of stiction allows very high velocities, while the maximum velocity is limited principally in stick-slip operation. In this part it is shown that slip-slip operation is also suitable for use with real actuators, driven with frequency-limited versions of the ideal signals presented in part I. The motional performance of the motor as well as its wear and the required electric power are investigated for operation with different signals. It is found that for high velocity inertia motors it is recommendable to use actuators with large stroke and to drive them with a signal consisting of two harmonics at a high fundamental frequency, a result that is supported by similar setups implemented experimentally by other authors. Using Lanczos' σ factors to calculate the frequency-limited excitation signals instead of standard Fourier series additionally increases the motor performance significantly. The results help motor designers to choose the appropriate mode of operation and to optimise the motor parameters for their individual applications.
Keywords: Inertia motor

Stick-slip and slip-slip operation of piezoelectric inertia drives - Part I: Ideal Excitation. - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Piezoelectric inertia motors, also known as ``stick--slip drives'', use the inertia of a body to drive it in small steps by means of a friction contact. While these steps are classically assumed to involve stiction and sliding, the motors can also operate in ``slip--slip'' mode without any phase of static friction. This contribution provides a systematic investigation and performance comparison of different stick--slip and slip--slip modes of operation. Different criteria for comparing the motional performance of inertia motors are defined: Steady state velocity, smoothness of motion, and start-up time. Using the example of a translational inertia motor excited by an ideal displacement signal, it is found that the maximum velocity reachable in stick--slip operation is limited principally, while continuous slip--slip operation allows very high velocities. For the investigated driving signals, the motor velocity is proportional to the square root of the actuator stroke. The motor performance with these ideal signals defines an upper boundary for the performance of real motors.
Keywords: Inertia motor; Stick--slip drive; Mode of operation; Performance indicator; Velocity maximization; Actuator stroke

Selected Papers from the 9th International Workshop on Piezoelectric Materials and Applications in Actuators (Sensors and Actuators A: Physical)
The 9th International Workshop on Piezoelectric Materials and Applications in Actuators (IWPMA 2012) was successfully held on 22–25 April 2012 in Hirosaki, Japan. The general chair was Prof. M.K. Kurosawa from the Tokyo Institute of Technology, Japan. In the past, Korea, Germany, Turkey, China, and USA have hosted the annual conference, but this was the first time for the annual IWPMA conference to be held in Japan. The IWPMA 2012 was organized as a joint symposium with JTTAS Smart Actuator/Sensor Study Committee and ICAT International Actuator Symposium. More than 150 people from the world (12 countries) participated and had fruitful discussions with 138 presentations including 11 invited talks. In addition to piezoelectric materials and piezoelectric actuators, the presentation topics were expanded to include solid-state actuators, energy harvesting, multifunctional materials, and other current important issues. It is our honor to pronounce that the “Sensors and Actuators A” journal has published this special issue on the IWPMA 2012 including the best 25 contributions. This issue covers the functional materials, such as piezoelectric and magnetostrictive materials, and their applications. However, for the innovative devices, various ideas concerning materials, mechanisms, designs, fabrication process, and control-systems are also required to be organically combined. From the view of this concept, we believe the published 25 papers can excite the researcher's intellectual curiosity concerning these issues and can serve as the driving force for further breakthroughs. Please enjoy the latest research results selected by our editor team. Finally, we appreciate all participants in the IWPMA 2012 and the devoted reviewers for the publication. We hope that the papers in this special issue will open up the next researches, which will be presented in the future IWPMA conferences.

Study on optimizing ultrasonic irradiation period for thick polycrystalline PZT film by hydrothermal method - Ohta, Kanako; Isobe, Gaku; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics)
The hydrothermal method utilizes a solution-based chemical reaction to synthesize piezoelectric thin films and powders. This method has a number of advantages, such as low-temperature synthesis, and high purity and high quality of the product. In order to promote hydrothermal reactions, we developed an ultrasonic assisted hydrothermal method and confirmed that it produces dense and thick lead--zirconate--titanate (PZT) films. In the hydrothermal method, a crystal growth process follows the nucleation process. In this study, we verified that ultrasonic irradiation is effective for the nucleation process, and there is an optimum irradiation period to obtain thicker PZT films. With this optimization, a 9.2-$μ$ m-thick PZT polycrystalline film was obtained in a single deposition process. For this film, ultrasonic irradiation was carried out from the beginning of the reaction for 18 h, followed by a 6 h deposition without ultrasonic irradiation. These results indicate that the ultrasonic irradiation mainly promotes the nucleation process.
Keywords: Piezoelectric material

Piezoelectric Properties of CuO-Doped (K,Na)NbO3 Lead-Free Ceramics Synthesized with Hydrothermal Powders - Yokouchi, Yuriko; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Japanese Journal of Applied Physics)
We report the piezoelectric properties of CuO-doped hydrothermal (K,Na)NbO3 ceramics that can be applied as hard-type lead-free piezoelectric ceramics. To date, we have succeeded in synthesizing high-quality KNbO3 and NaNbO3 powders by the hydrothermal method, which is based on an ionic reaction at high temperature (around 210 $\,^{°}$C) and pressure. Increasing both the piezoelectric constant d and the mechanical quality factor (Qm) is important for resonance-type piezoelectric devices, such as ultrasonic motors and transformers. CuO doping into hydrothermal (K,Na)NbO3 ceramics was examined to realize hard-type lead-free piezoelectric ceramics. By doping with 1.2 mol % CuO, Qm was increased and the dielectric loss (tan δ) was decreased to 0.5%. The grain size was also influenced by the amount of CuO doping, which indicates that Qm is related to the density. To achieve a higher Qm value, the grain size is required to be less than 5 µm; however, excessive CuO doping leads to anomalous grain growth. Optimal piezoelectric properties were obtained for 1.2 mol % CuO-doped (K,Na)NbO3; k31 = 0.32, d31 = -44 pC/N, Qm (radial) = 959, and tan δ= 0.5%. These characteristics showed that CuO doping with hydrothermal powders is effective for obtaining hard-type ceramics, and the mechanical quality factor is more than ten times higher than that of nondoped hydrothermal (K,Na)NbO3 ceramics. Therefore, compared with the conventional solid-state method, we could succeed in obtaining hard-type ceramics by a simple and short process.

Frequency tuning of piezoelectric energy harvesters by magnetic force - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Smart Materials and Structures)
A piezoelectric energy harvester is an electromechanical device that converts ambient mechanical vibration into electric power. Most existing vibration energy harvesting devices operate effectively at a single frequency only, dictated by the design of the device. This frequency must match the frequency of the host structure vibration. However, real world structural vibrations rarely have a specific constant frequency. Therefore, piezoelectric harvesters that generate usable power across a range of exciting frequencies are required to make this technology commercially viable. Currently known harvester tuning techniques have many limitations, in particular they miss the ability to work during harvester operation and most often cannot perform a precise tuning. This paper describes the design and testing of a vibration energy harvester with tunable resonance frequency, wherein the tuning is accomplished by changing the attraction force between two permanent magnets by adjusting the distance between the magnets. This tuning technique allows the natural frequency to be manipulated before and during operation of the harvester. Furthermore the paper presents a physical description of the frequency tuning effect. The experimental results achieved with a piezoelectric bimorph fit the calculated results very well. The calculation and experimental results show that using this tuning technique the natural frequency of the harvester can be varied efficiently within a wide range: in the test setup, the natural frequency of the piezoelectric bimorph could be increased by more than 70%.